2018
DOI: 10.1039/c7ra12931a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of toluene with water on zeolitic imidazolate framework-8/graphene oxide hybrid nanocomposites in a humid atmosphere

Abstract: ZIF-8/GO composites can be used as efficient and recyclable adsorbents for the removal of toluene with water in a humid atmosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 26 publications
(35 reference statements)
3
15
0
Order By: Relevance
“…[5] Studies on ZIF-8 powders have found the materials are suitable adsorbents for several applications including vapor phase hydrocarbon capture [6][7][8] and liquid-phase contaminant extraction. [9,10] Due to the hydrophobicity of the 2-methylimidazole linker, ZIF-8 has been found to have low affinity toward water vapor, [6,11] making it particularly suitable for adsorption applications where humidity's competition for adsorption sites plays a key role, [12,13] such as indoor air cleaning of volatile organic compounds (VOCs). [14][15][16] ZIF-67 has been found to be unstable in liquid water, with a noted loss in crystallinity, [17] and water vapor isotherms of the material have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Studies on ZIF-8 powders have found the materials are suitable adsorbents for several applications including vapor phase hydrocarbon capture [6][7][8] and liquid-phase contaminant extraction. [9,10] Due to the hydrophobicity of the 2-methylimidazole linker, ZIF-8 has been found to have low affinity toward water vapor, [6,11] making it particularly suitable for adsorption applications where humidity's competition for adsorption sites plays a key role, [12,13] such as indoor air cleaning of volatile organic compounds (VOCs). [14][15][16] ZIF-67 has been found to be unstable in liquid water, with a noted loss in crystallinity, [17] and water vapor isotherms of the material have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…68,69 Toluene has been widely adopted in various industrial processes, and has thus caused serious air pollution and social health hazard effects. 70,71 Accordingly, MOFs, one of most attractive adsorbents, exhibited great potential for capturing and removing toluene with low concentrations (<1000 ppm v ). [71][72][73] Fig.…”
Section: Resultsmentioning
confidence: 99%
“…benzene, toluene, and xylene (BTX) are the major members of VOCs pollutions. These VOCs are preferably adsorbed on hydrophobic surfaces as compared to hydrophilic surfaces [74][75]. The previously results showed, the GO may exhibit less adsorption capacity for aromatic VOCs.…”
Section: Sorbent Methodsmentioning
confidence: 84%
“…Several attempts have been made to eliminate or recover VOCs from wastewater; for example, distillation is commonly used, regardless of azeotropes formation or high energy consumption [6,7,10,12,[26][27][28][29]. Hitherto, a number of approaches including adsorption [30][31][32], condensation [33], incineration [34,35] and thermal oxidation [36] have been established to eliminate VOCs from the environment. Treatment methods that have been established for VOCs removal are as follows: air stripping, adsorption, advance oxidation, distillation, anaerobic/aerobic biological treatment and the technology of membrane [27,29,[37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%